DDoS mitigation: a review of content delivery network and its DDoS defense techniques - Imthiyas, Mohammed; Wani, Sharyar; Abdulghafor, Rawad Abdulkhaleq Abdulmolla; Ibrahim, Adamu Abubakar; Hafeez, Abdul (International Journal on Perceptive and Cognitive Computing (IJPCC), 2020)
Distributed Denial-of-Service (DDoS) attacks continue to pose major threats overwhelming entire networks. They slacken the availability of Internet service by sending huge malicious requests and spreading volumetrically. This survey recognizes fundamental theories across various disciplines to advance and improve the research of DDoS mitigation. These studies focus on DDoS mitigations with Content Delivery Network (CDN) from two views: (1) CDN’s layout model and (2) its DDoS defense classifications. Content Delivery Network (CDN) refers to the Internet and delivers contents to the end-users. CDN is used for the basis of reverse proxying, web serving, and load balancing, etc. This literature finds that CDN serves clients from a scalable set of proxies that automatically deploys multiple websites. It protects the websites against DDoS and categorizes each view with various suitable defense methods. By reviewing DDoS mitigation characteristics among the DDoS attacks, this study features some possible methods to mitigate DDoS attacks with Content Delivery Network (CDN).